2014
DOI: 10.4172/2155-6156.1000377
|View full text |Cite
|
Sign up to set email alerts
|

A Retrospective Study in 5,989 Patients with Type 1 Diabetes in 10 Outpatient Diabetes Clinics in Sweden of the Frequency of Measuring HbA1c in Clinical Practice

Abstract: Aim: Guidelines for the treatment of type 1 diabetes generally recommend quarterly or more frequent Haemoglobin A1c (HbA1c) assessment in patients with inadequate glycaemic control. The purpose of the current study was to evaluate to what extent these guidelines are followed in clinical practice in Sweden. Method:We studied 5989 patients with type 1 diabetes from 10 outpatient diabetes clinics in Sweden from 1 January 2005 to 31 December 2009. Data on HbA1c measurement frequency were obtained from the Diab-Bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…This study provided important insight into HbA1c measurement in routine clinical practice in Sweden. It was found that the measurements were done less than that recommended by guidelines recommend[ 9 ] Prospective study: LANDMARC study is a prospective, multicenter study evaluating a large cohort of people with type 2 diabetes mellitus across India over a period of 3 years. This study will reveal the trends in complications associated with diabetes; treatment strategies used by physicians; and correlation among treatment, control, and complications of diabetes[ 10 ] Cross-sectional study: This multicenter study was designed to determine the control of dyslipidemia in the Indian diabetic population treated with lipid-lowering drugs.…”
Section: Example Of Real-world Evidence Studies Conducted In Indiamentioning
confidence: 99%
See 1 more Smart Citation
“…This study provided important insight into HbA1c measurement in routine clinical practice in Sweden. It was found that the measurements were done less than that recommended by guidelines recommend[ 9 ] Prospective study: LANDMARC study is a prospective, multicenter study evaluating a large cohort of people with type 2 diabetes mellitus across India over a period of 3 years. This study will reveal the trends in complications associated with diabetes; treatment strategies used by physicians; and correlation among treatment, control, and complications of diabetes[ 10 ] Cross-sectional study: This multicenter study was designed to determine the control of dyslipidemia in the Indian diabetic population treated with lipid-lowering drugs.…”
Section: Example Of Real-world Evidence Studies Conducted In Indiamentioning
confidence: 99%
“…This study provided important insight into HbA1c measurement in routine clinical practice in Sweden. It was found that the measurements were done less than that recommended by guidelines recommend[ 9 ]…”
Section: Example Of Real-world Evidence Studies Conducted In Indiamentioning
confidence: 99%
“…2-5 Optimal control is only achieved by a few with T1D worldwide, specifically 21% in the United States. 6-10…”
Section: Introductionmentioning
confidence: 99%
“…Globally, diabetes mellitus is considered to be an epidemic and a growing burden on public health (Matuleviciene, et al, 2014). It is associated with a significant morbidity and mortality (Schwartz & Scheiner, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…It is associated with a significant morbidity and mortality (Schwartz & Scheiner, 2012). It has been estimated that 385 million people worldwide live with Diabetes and the number is predicted to rise to 500 million in 2030 (Matuleviciene, et al, 2014). In the UK, there are some four million people diagnosed with diabetes and an estimated additional 590,000 that are not yet diagnosed (Diabetes UK, 2015).…”
Section: Introductionmentioning
confidence: 99%